Hukum Perlindungan Konsumen dalam Transaksi Elektronik dan E-Commerce - Kadek Sri Candra Laksmi Putri,; Ni Ketut Sari Adnyni,; Made Sugi Hartono, (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of information technology has significantly transformed commercial activities, particularly through the emergence of electronic transactions or e-commerce. The convenience offered by digital trading systems provides various benefits for both consumers and business actors, such as time efficiency, ease of access, and broader market reach. However, behind these advantages, there are also several risks that may harm consumers, including discrepancies between product descriptions and actual goods, delivery delays, and potential online fraud. This study aims to analyze the legal protection for consumers in electronic transactions and the responsibilities of business actors within digital commerce systems. This research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that consumer legal protection in electronic transactions has been regulated in various laws and regulations; however, in practice, several challenges remain in its implementation. Therefore, strengthening regulations, enhancing supervision of business actors, and increasing public legal awareness are necessary to create a safer electronic transaction system and ensure legal certainty for consumers.